Profile of Female Individuals with Chronic Low Back Pain - Bijoya Dey Happy,; Afzal Hossain,; Md Hasibul Islam,; Sanjida Pervin,; Shaifur Ahmed,; Md Atikul Aziz,; Aparajeya Bivab Bikash Baral, (KYAMC Journal, 2025)
Background: When low back pain (LBP) persists for at least 12 weeks, it becomes chronic. In 90% of cases, LBP is satisfactorily resolved within 6 weeks. LBP becomes chronic in 7% to 10% of cases. Among various populations, females tend to experience a higher prevalence and severity of chronic LBP compared to males, attributed to a combination of anatomical, hormonal, psychosocial and occupational factors. Objective: To see the profile of individuals with chronic low back pain (CLBP) in female patients. Materials and Methods: This observational study was carried out at the Department of Physical Medicine and Rehabilitation, BSMMU, Dhaka in 2016. 150 female patients of low back pain attending the Physical Medicine and Rehabilitation department, BSMMU were enrolled. Purposive sampling was done according to availability of the patients. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using SPSS. Results: Most of the patients belonged to low educational group (n=60, 40%). Obesity was an important risk factor for developing chronic low back pain. Patients with overweight were found, 43.33% (n=65). The most of the patients were in 5000 to15000 taka income group (n=90, 60%) whereas 41 patients (27.33%) family members were suffering from CLBP, and 76.0% (n=114) were inactive from physical exercise (Grade 1). 121 patients (80.66%) had the experience of grade 3 bad posture. Conclusion: People in the grade 1 level of exercise group had the highest risk of developing CLBP. People in the grade 3 (regular) bad posture group had the highest risk of developing CLBP. KYAMC Journal. 2024; 15(02): 77-82